HUBUNGAN KUAT GESER DENGAN PLASTISITAS, FRAKSI TANAH DAN MINERAL TANAH LEMPUNG DAERAH BENDUNGAN GUNUNG ROWO DAN TOL JATINGALEH – KRAPYAK KM 5+525 - Savitri Eka Putri; Nurkhasanah Rina Puspita; muhrozi muhrozi; Indrastono Dwi Atmono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Indonesia is a disaster-prone area to landslides and Indonesia has widely spread of clay soils, so that continuous the study of clay is necessary about characteristics of clay soil. The purpose of this study is to determine the empirical relationship plasticity values, fractions and mineral soil and to predict the effective shear strength c’ and f’. Analysis is about linier regression to infer the relationship between effective shear strength c’ and f’ with plasticity values, fractions and mineral soils, then analyze slope stability on Tol Jatingaleh – Krapyak. The results showed that LL and PI are more large then c’ value is more large too, but it is reverse about PL. If PL is more large then c’ is more sligthly If value of c soils is more large then c’ is more large too, on the contrary if it is f’ soils. Soils with a large content of montmorillonite tend to have great cohession. Decreasing of montmorilonite, it means that value of c’ is more slightly because rise of illite and kaolinite. Further research is indispensible to get enough data to do non-linier regression and multivariate regression to produce a reliable value R > 0,9.